KECEMASAN MAHASISWA NON BAHASA INGGRIS DALAM PEMBELAJARAN SPEAKING - Nasrullah Nasrullah; Isna Humaera; Sahril Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this study is to discover how students in the non-English department at the University Muhammadiyah of Parepare feel about learning English. Based on the perspectives of the students, this study sought to identify what factors may contribute to anxiety in an English learning environment. In this case, researchers prioritize the perspectives of students who are not English majors on the anxiety they frequently experience when learning English. The researcher used a case study to conduct qualitative research. While the participants in this study were students from Muhammadiyah University in Parepare for the academic year 2021/2022, the purposive sampling technique was used to select 7 non-English department students. The chosen samples would be interviewed to obtain detailed information about the data required. The findings of this study revealed that students had many concerns about learning English. The majority of respondents also admitted that English is difficult to learn because they lack basic abilities, such as a lack of vocabulary and the complexity of the material learned, which can make students feel confused and difficult to learn English. Furthermore, comments from other friends, such as the incorrect pronunciation of English vocabulary, affect their feelings. Respondents also revealed that lecturers' ability to bring material can influence their feelings about learning English. In the end, the students suggested that the lecturer be more creative to keep students interested in learning English, such as bringing in an outdoor concept and providing some games for the learning process